FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN OBESITAS SENTRAL PADA WANITADEWASA (30-50 TAH UN) DI KECAMATAN LUBUK SIKAPING TAHUN 2008 - Ida Trisna; Sudiharti Hamid (Jurnal Kesehatan Masyarakat Andalas, 2009)
Nutritionproblem in Indonesia now is recognized as multiple Nutritionproblem (double burden) where Faced in the form of less and over nutrition. It happened not only in urban but also in rural area. High energy intake not in concurrently with physical activity will result in energy excess stored in adipose tissue in unlimited number. With the increasing of age. the increasing of adipose cell at woman 30-50 years happened significantly. Waist circumference Measurement is one way of assessing fat hoard in stomach. This research was aimed to know The relation of energy intake, carbohydrate, fat and physical activities with obesity central at women (30-50 years) Kecamatan Lubuk Sikaping Kabupaten Pasaman 2008. This research type is cross sectional study, with test chi-square, analyzed in univariat, bivariate and multivariat. Sample amounts to / 73 people who selected in stratified random sampling; data was collected through interview with the instrument of questionnaire and conducted in March until June 2008 in Kecamatan Lubuk Sikaping Pasaman. Prom this research were found central obesity prevalence of 49, 7%, with average of energy intake from carbohydrate percentage higher than recommended. This research concludes that there is significant relationship between intakeof energy, carbohydrate, fat and physical activity with central obesity. From multivariate analysis wasfound that responder with average of energy intake from percentage carbohydrate > 60% is 10,9 times in risk. From result of this research it is expected to related institution and the community to intensify the program preventive and in handling over nutrition by socializing PUGS periodically and without disregarding the problem of less nutrition.